PENERAPAN METODE PEMBELAJARAN OUTDOOR LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPAS - Delia Silvi Setiani; Ilyas Idris; Ica Wandari Anisia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low academic achievement of third-grade students at MI Rahmatullah in Jambi City in the subjects of Natural Sciences and Social Studies. This is due to a teaching approach that remains teacher-oriented, causing students to tend to be passive, lack enthusiasm, and become easily bored. This classroom action research (PTK) was conducted in two cycles with 21 students as subjects, aiming to improve learning outcomes through the application of the Outdoor Learning method. The results showed a significant improvement from Cycle I to Cycle II, with the average test score rising from 61.90% to 80.95%—an increase of 19.05%. Teacher activity increased from 55.56% to 88.89%, and student activity rose from 53.44% to 77.25%. This proves that there is a significant difference between student learning outcomes in Cycle I and Cycle II. Improvement efforts were carried out through systematic refinements in the application of the Outdoor Learning method, including outdoor learning activities centered on the theme of energy and its transformations, where students directly observed energy sources around the school and explored various ways to conserve energy. In conclusion, the structured and systematic implementation of the outdoor learning method effectively improved third-grade students’ learning outcomes in Natural and Social Sciences; therefore, it is recommended that teachers continue to apply this method using a variety of techniques tailored to students’ characteristics.